023 Platelet activation induces phenotypic and functional changes in circulating monocytes as a consequence of monocyte–platelet aggregate formation. (22nd September 2015) - Passacquale, G; Corrigall, V; Hamid, C; Ferro, A
Abstract : Background and Hypothesis: Circulating levels of monocyte-platelet aggregates (MPAs) increase in response to platelet activation, and have previously been shown to be elevated in patients presenting with acute cardiovascular (CV) events and in healthy subjects who have underlying CV risk factors. MPAs are also believed to be crucial mediators involved in the pathophysiology of atherosclerosis. Since circulating monocytes comprise different sub-populations which can infiltrate and migrate into tissues to differing degrees, we hypothesised that activated platelets may enhance their differentiation towards a pro-atherogenic phenotype. Methods: MPAs and monocytes in peripheral blood obtained from healthy volunteers were measured and characterised by FACS analysis. Additionally, monocytes were isolated through immunomagnetic negative selection for CD14+/CD16− cells and co-incubated with autologous platelets. Flow cytometry and adhesion assays on pre-activated endothelial cells (treated with TNF-α 10 ng/ml for 3 h) were performed at different time points. Results: Three monocytic subsets were identified in blood: classical CD14+/CD16−, CD14high/CD16+ and CD14low/CD16+ cells. They displayed different expression patterns of the adhesion molecules CD11b and CD11c, although no difference was found in their ability to form MPAs in vivo. Platelet co-incubation enhanced monocyte phenotypic change toward CD14+/CD16+ double positivity in a time-dependent manner (33.33±7.79% vs 16.76±6.34% at 48h in the presence or absence of platelets respectively; p=0.0001), with CD16 expression being directly correlated to MPA levels (r 2 =0.746; p=0.005). This phenotypic change was associated with enhanced monocyte adhesion to activated endothelium (11.5±1.7 vs 5.7±1.5 cells per field, when co-incubated or not with platelets respectively; p=0.005). Adhesion assay demonstrated that only cells positive for both CD14 and CD16 could bind to endothelium, while classical CD14+/CD16− monocytes could not (Abstract 023 Figure 1a ). In keeping with this, the sub-population of CD14+/CD16+ monocytes exhibited higher levels of both CD11b and CD11c on the cell surface compared to the monocyte sub-population only positive for CD14. PSGL-1 blocking antibody, which abrogates monocyte-platelet interaction, abolished all these effects (Abstract 023 Figure 2 ). Moreover, induction of cyclooxygenase 2 (COX-2) was observed in monocytes at 18 h of co-incubation with platelets (Abstract 023 Figure 1b ), and specific blockade of COX-2 with NS-398 (10 μM) reduced platelet-dependent CD16 upregulation in CD14+ monocytes, without affecting MPA formation in vitro (Abstract 023 Figure 2 ). Conclusion: Platelet interaction upregulates CD16 and expression of adhesion molecules on monocytes, in a COX-2-dependent manner, resulting in greater adhesion to the endothelium.